"Better get to know Practicum: Critical Theory, Religion, and Pedagogy" an interview with Craig Martin and Brad Stoddard of Practicum blog. (10th November 2015) - Chatterjea, Ipsita
Abstract : Part of a recurring series on the Bulletin for the Study of Religion blog, "Better get to know..." profiles the groups that groups and organizations that support the analysis of, teaching of, media covering analytical scholarship focused on religion. This installment profiles Practicum: Critical Theory, Religion, and Pedagogy, through a conversation Craig Martin and Brad Stoddard.